A Critical Role for Extracellular DNA in Dental Plaque Formation. (February 2017) - Rostami, N.; Shields, R.C.; Yassin, S.A.; Hawkins, A.R.; Bowen, L.; Luo, T.L.; Rickard, A.H.; Holliday, R.; Preshaw, P.M.; Jakubovics, N.S.
Extracellular DNA (eDNA) has been identified in the matrix of many different monospecies biofilms in vitro, including some of those produced by oral bacteria. In many cases, eDNA stabilizes the structure of monospecies biofilms. Here, the authors aimed to determine whether eDNA is an important component of natural, mixed-species oral biofilms, such as plaque on natural teeth or dental implants. To visualize eDNA in oral biofilms, approaches for fluorescently stained eDNA with either anti-DNA antibodies or an ultrasensitive cell-impermeant dye, YOYO-1, were first developed using Enterococcus faecalis, an organism that has previously been shown to produce extensive eDNA structures within biofilms. Oral biofilms were modelled as in vitro "microcosms" on glass coverslips inoculated with the natural microbial population of human saliva and cultured statically in artificial saliva medium. Using antibodies and YOYO-1, eDNA was found to be distributed throughout microcosm biofilms, and was particularly abundant in the immediate vicinity of cells. Similar arrangements of eDNA were detected in biofilms on crowns and overdenture abutments of dental implants that had been recovered from patients during the restorative phase of treatment, and in subgingival dental plaque of periodontitis patients, indicating that eDNA is a common component of natural oral biofilms. In model oral biofilms, treatment with a DNA-degrading enzyme, NucB from Bacillus licheniformis, strongly inhibited the accumulation of biofilms. The bacterial species diversity was significantly reduced by treatment with NucB and particularly strong reductions were observed in the abundance of anaerobic, proteolytic bacteria such as Peptostreptococcus, Porphyromonas and Prevotella . Preformed biofilms were not significantly reduced by NucB treatment, indicating that eDNA is more important or more exposed during the early stages of biofilm formation. Overall, these data demonstrate that dental plaque eDNA is potentially an important target for oral biofilm control.